2017
DOI: 10.1007/s40843-017-9104-9
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-low charge transfer resistance carbons by one-pot hydrothermal method for glucose sensing

Abstract: Hydrothermal carbon (HTC) is typically welldispersed, but it remains a great challenge for HTC to become conductive. Co-doping with heteroatoms has been confirmed to be an effective strategy to significantly promote the electrical conductivity of carbon. Moreover, there is no simple and green method to construct sensitive HTC based electrochemical biosensors until now. In this paper, N and S dualdoped carbon (NS-C) with ultra-low charge transfer resistance is easily synthesized from L-cysteine and glucose in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 58 publications
(76 reference statements)
0
2
0
1
Order By: Relevance
“…The peaks centered at 1350 and 1580 cm −1 correspond to the D and G band, respectively (Figure 1I). 35 The D band represents the subsistent disorder carbon structures, and the G band corresponds to the vibration of sp 2 ‐hybridized C atoms in the graphitic layer. The peak intensity ratio of D and G bands ( I D / I G ) is regarded as an index of the graphitization degree 18 : the high I D / I G value for GOC‐4 indicated that a higher number of defects were generated with increased KOH/GOCs ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The peaks centered at 1350 and 1580 cm −1 correspond to the D and G band, respectively (Figure 1I). 35 The D band represents the subsistent disorder carbon structures, and the G band corresponds to the vibration of sp 2 ‐hybridized C atoms in the graphitic layer. The peak intensity ratio of D and G bands ( I D / I G ) is regarded as an index of the graphitization degree 18 : the high I D / I G value for GOC‐4 indicated that a higher number of defects were generated with increased KOH/GOCs ratios.…”
Section: Resultsmentioning
confidence: 99%
“…In traditional methods, the utilization of concentrated acids or alkalis in industrial processes necessitates the use of equipment capable of withstanding high temperatures, pressures, and corrosive environments. However, achieving adequate stirring under these conditions poses a challenge, making large-scale reactor production technically intricate and costly [8][9][10][11]. To address these issues, high-frequency travelingwave magnetic field drive technology offers a solution by enabling non-contact stirring and heating of the electrolyte within enclosed reactors.…”
Section: Introductionmentioning
confidence: 99%
“…Biomass can be pyrolyzed under anaerobic or oxygen-limited conditions to obtain carbonrich, highly aromatic, and porous solid biochar materials [11], which possess abundant pore structures, a large specific surface area, and rich oxygen-containing functional groups on their surface. Biochar materials also exhibit excellent optical, electrical, mechanical, and chemical properties, finding wide applications in the fields of environment and energy [11][12][13][14][15]. The methods for preparing biochar materials include the template method [11], chemical vapor deposition (CVD) [12], high-temperature pyrolysis [13], and hydrothermal carbonization [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Biochar materials also exhibit excellent optical, electrical, mechanical, and chemical properties, finding wide applications in the fields of environment and energy [11][12][13][14][15]. The methods for preparing biochar materials include the template method [11], chemical vapor deposition (CVD) [12], high-temperature pyrolysis [13], and hydrothermal carbonization [14][15][16]. Among them, hydrothermal carbonization is an exothermic reaction in which carbohydrates are used as raw materials and water serves as the reaction medium.…”
Section: Introductionmentioning
confidence: 99%